Effectiveness of Saffron against Hepatotoxicity Caused by Silver Nanoparticles in Vivo - Galawesh Norri Taher (Pakistan Journal of Medical & Health Sciences, 2022)
Adverse effects of silver nanoparticles (Ag-NPs) on health remain a concern. This research study was performed to appreciate the activity of saffron plant (SAF) upon Ag-NPs-induced hepatotoxicity. Eighteen male rats were consumed, separated into three groups of equal numbers. The animals of the group (CON) were not dosed with either treatment, while the animals of the group (Ag-NPs) were treated with Ag-NPs orally. In the latter group (Ag-NPs + SAF) intoxicated rats with Ag-NPs were provided with SAF. The experiment lasted seven days. The study found that dosing with Ag-NPs led to a considerable elevates in serum levels of biochemical parameters of liver function and hepatic oxidative stress, while significantly diminished glutathione activity. But the combined use of SAF extract improved the disturbed hepatic parameters. It was concluded that SAF could efficaciously mitigate Ag-NPs-induced liver toxicity in vivo. More investigations are needed to determine the exact mechanisms behind affront’s ability to protect the liver.